(3EVGAI GdQGehSs - (3eMeO Hf GdWjH eMeO Hf eMeO Hf eMeO GdTQbj GdaGSj GdeGdcj, CHh YHO Gddg , J (B1170 (3g`s; (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s
(3ChdgG (B:s
(3HGH GdMGA GdegedI bdJ bO CHOdhgG ef GdYjf ai bhdge QjM HOd bhdge QjY s
(3BNQgG (B:s
(3bGd GdTgGH GdYSbdGfi ai EQTGO GdSGQi ChGFd GdEjeGf Cf EHQGgje GdNdjd Ydjg GdSdGe hGdgd SHMGfg hJYGdi CYde s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B147s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs